2021
DOI: 10.1159/000514154
|View full text |Cite
|
Sign up to set email alerts
|

Decline and Recurrence of Stroke Consultations during the COVID-19 Pandemic Lockdown Parallels Population Activity Levels

Abstract: <b><i>Background:</i></b> The COVID-19 pandemic lockdown (CPL) lead to a significant decrease in emergency admissions worldwide. We performed a timely analysis of ischemic stroke (IS) and related consultations using the telestroke TEMPiS “working diagnosis” database prior (PL), within (WL), and after easing (EL) of CPL. <b><i>Methods:</i></b> Twelve hospitals were selected and data analyzed regarding IS (including intravenous thrombolysis [intravenous recombinant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…However, data of all remaining telemedical networks showed a reciprocal increase of telemedical consultations after relaxation of COVID-19 measures, leading us to the assumption that a substantial bias is unlikely. Sixth, data of the TEMPiS network were already published [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, data of all remaining telemedical networks showed a reciprocal increase of telemedical consultations after relaxation of COVID-19 measures, leading us to the assumption that a substantial bias is unlikely. Sixth, data of the TEMPiS network were already published [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Single-center observations from the United States and Germany report a significant decline in teleconsultations during the peak phase of the COVID-19 pandemic in March and April 2020 [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…They performed the analysis prior to, within, and after easing of lockdown. They concluded that the decrease in emergency admissions for stroke during the pandemic was largely attributed to patients not seeking medical attention and a lack of stroke awareness (36). There are further reports showing a similar trend of time-dependent declines in hospitalization for stroke during the pandemic and nationwide lockdowns (37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Stroke Care During Covid-19mentioning
confidence: 99%
“…Patients with AIS continued to receive acute recanalization treatment (35). Schlachetzki et al analyzed data related to ischemic stroke from 12 hospitals; intravenous (IV) thrombolytic treatment, endovascular treatments (EVT), and related consultations using the telestroke (stroke telemedicine) TEMPiS "working diagnosis" were analyzed (36). They performed the analysis prior to, within, and after easing of lockdown.…”
Section: Stroke Care During Covid-19mentioning
confidence: 99%
“…[1][2][3][4] The burden of these illnesses impacts mostly low-to middle-income countries, where larger percentage of the world's population also continue to suffer the consequences of the ongoing pandemic. [5][6][7] In this context, the World Federation of Neurology (WFN) World Brain Day (WBD) campaign is of particular importance. Since the inception of the WBD campaign in 2014, this global advocacy initiative has been very successful.…”
mentioning
confidence: 99%